Meningkatkan Aktivitas dan Hasil Belajar Siswa Muatan IPS Menggunakan Model Panting - Hela Mardiah; Wahdah Refia Rafianti (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem of this research is the low student activity and student learning outcomes of social studies content in class V SDN Sepakat Bersama Barito Kuala. The causes of these problems in the teacher's learning process only use the lecture method, students' activeness in the learning process is less visible, and the learning atmosphere is not pleasant. With the problems previously described, the researcher made improvements by combining several learning models, namely the Problem Based Learning, Group Investigation and Snowball Throwing (PANTING) models in the learning process. The research objective is to analyze student learning activities and outcomes. This study used Classroom Action Research (CAR) which was held in 4 meetings and used qualitative and quantitative data. The results showed that the activity of the teacher at meeting I achieved a score of 26 "good" criteria and at meeting IV achieved a score of 35 criteria of "very good". Observation of student activity at meeting I obtained 53.33% of the criteria of "quite active" and at meeting IV 100.00% of the criteria of "very active". Classical completeness of student learning outcomes at the first meeting obtained 53.33% of students "completed" and meeting IV reached 100.00% of students "completed". Based on these findings it can be concluded that the combination of several models can increase student activity and learning outcomes.